(3GbJUGOjGJ GdehGQO hGdHjFI (B/s - (3ajTQ, S(B.(3GfWhfjs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2002)
(3GdehGQO GdfGHVI(B: (3fXQjI GdGSJfRGa GdGeKd(B, (3GdehGQO GdeJLOOI(B: (3fXQjI GdGSJNOGe GdGeKd GVGaI Gdi fOQI GdehGQO (B( (3gd JbjO GdehGQO Gdfeh(B) (3h cPG GdehGQO GdWHjYjI h GdHjFGJ GdWHjYjI(B, (3GdJdhK GdHjFj h GNjQG HYV GdGacGQ GdNJGejI (B( (3OhQ GdGbJUGO aj OQGSI eTGcd GdehGQO h GdHjFI(B).s
(3eQGLY U(B.247s
Keywords: (3GbJUGOjGJs; (3GdHjFIs; (3GdehGQO GdGbJUGOjIs